To buy or not to buy a "counterfeit" Ralph Lauren polo shirt: the role of lawfulness and legality toward purchasing counterfeits - Phau, Ian; Sequeira, Marishka; Dix, Steve (Emerald Group Publishing Limited, 2009)
This study examines the influence of personality factors and attitudes toward consumers' willingness to knowingly purchase counterfeit luxury brands. Convenience sampling method was employed and a self administered questionnaire was distributed to students in a large Australian university. A commonly counterfeited luxury branded product was used as the stimulus of the study. 202 useable responses were retained for analysis. The findings found that attitudes do not influence consumers' willingness to purchase counterfeit luxury brands. Integrity has been noted to be a strong influencer of both attitudes and consumer willingness to purchase consistently. Both buyers and non- buyers were tested for their attitudinal differences. Status consumption and materialism did not play a role in influencing attitudes or willingness to purchase. Only one product category was looked at. Other sampling methods can be looked into such as mall intercept. Culture and nationality may also have influences on moral and ethical issues which can be tested in future studies. Advertisers and strategists should consider putting a more 'human face' on the damaging effects of counterfeiting and look into the possible demographic factors. Consumers should be educated on the negative consequences of counterfeiting and effects on economy. While past studies have delved into examining consumer attitudes towards counterfeit products, a low involvement luxury brand item was not utilized as a stimulus. An Australian context has not been looked into.